System dynamics scenarios for sustainable oil palm management toward Indonesia’s 2060 net zero target - ENDANG HERNAWAN; MIA ROSMIATI; TIEN LASTINI; ERI MUSTARI; MAMAT KANDAR (Smujo International, 2025)
Abstract. Hernawan E, Rosmiati M, Lastini T, Mustari E, Kandar M. 2025. System dynamics scenarios for sustainable oil palm management toward Indonesia’s 2060 net zero target. Asian J Agric 9: 402-414. Indonesia’s palm oil sector plays a crucial role in national economic growth. However, it faces complex and interconnected challenges, including maintaining its significant contribution to GDP, supporting the expansion of biodiesel production, complying with the European Union’s deforestation regulations, and fulfilling commitments under the Nationally Determined Contribution (NDC) by 2030, as well as the national target of achieving net-zero emissions by 2060. This study aims to identify an ambitious yet realistic pathway for sustainable palm oil plantation management through the development and application of a system dynamics model. The research uses secondary data sources, including national palm oil production statistics, demographic trends, economic indicators, and policy documents related to palm oil governance and climate change mitigation. The Indonesia Sustainability of Oil Palm Plantations Management (ISOPPM) model was designed to simulate the impacts of policy interventions focused on promoting the use of organic fertilizers, distributing superior oil palm seedlings, and expanding B40 biodiesel production. The model’s accuracy and reliability were tested by comparing simulated results with historical data from national statistics. The results indicate that under the ambitious scenario, crude palm oil production could increase by 81.3% compared to the business-as-usual scenario. In comparison, plantation area expansion could be limited to 6.27%, enabling the sector to achieve net-zero greenhouse gas emissions as early as 2048. Furthermore, this scenario demonstrates the potential to mitigate forest biodiversity loss through more efficient land use and improved agricultural practices. Overall, the validated ISOPPM model indicates that with appropriate policy support and technological improvements, Indonesia’s palm oil sector can significantly enhance productivity, minimise deforestation risks and biodiversity loss, and contribute meaningfully to national climate goals, ensuring a balance between economic development, environmental protection, and long-term sustainability.